Reassembly of a tropical rainforest: A new chronosequence in the Chocó tested with the recovery of tree attributes - Sebastián Escobar; Felicity L. Newell; María‐José Endara; Juan E. Guevara‐Andino; Anna R. Landim; Eike Lena Neuschulz; Ronja Hausmann; Jörg Müller; Karen M. Pedersen; Matthias Schleuning; Constance J. Tremlett; Edith Villa‐Galaviz; et al. (Ecosphere)
Abstract From hunting and foraging to clearing land for agriculture, humans modify forest biodiversity, landscapes, and climate. Forests constantly undergo disturbance–recovery dynamics, and understanding them is a major objective of ecologists and conservationists. Chronosequences are a useful tool for understanding global restoration efforts. They represent a space‐for‐time substitution approach suited for the quantification of the resistance of ecosystem properties to withstand disturbance and the resilience of these properties until reaching pre‐disturbance levels. Here, we introduce a newly established chronosequence with 62 plots in active cacao plantations and pastures, early and late regeneration, and old‐growth forests in the extremely wet Chocó rainforest. Plots were located across a 200‐km2 area, with a total area of 95 km2 within a 1‐km radius. Our chronosequence covers the largest total area of plots compared with others in the Neotropics with 15.5 ha. Plots ranged from 159 to 615 m above sea level in a forested landscape with 74% ± 2.8% forest cover within a 1‐km radius including substantial old‐growth forest cover. Land‐use legacy and regeneration time were not confounded by elevation. We tested how six forest structure variables (maximum tree height and dbh, basal area, number of stems, vertical vegetation heterogeneity, and light availability), aboveground biomass (AGB), and rarefied tree species richness change along our chronosequence. Forest structure variables, AGB, and tree species richness increased with regeneration time and are predicted to reach similar levels to those in old‐growth forests. Compared with previous work in the Neotropics, old‐growth forests in Canandé accumulate high AGB that takes one of the largest time spans reported until total recovery. Our chronosequence comprises one of the largest tree species pools, covers the largest total area of regenerating and old‐growth forests, and has higher forest cover than other Neotropical chronosequences. Hence, our chronosequence can be used to determine the time for recovery and stability (resistance and resilience) of different taxa and ecosystem functions, including species interaction networks. This integrative effort will ultimately help to understand how one of the most diverse forests on the planet recovers from large‐scale disturbances.